Analysis Dosage of Boron in BNCT with Simulation Method Using PHITS (Particle and Heavy Ion Transport Code System) Program - Jalut, Laura Laudensia Senly; Rupiasih, Ni Nyoman; Sardjono, Yohanes (BULETIN FISIKA; Vol 21 No 1 (2020): BULETIN FISIKA, 2020)
Abstrak – Cancer is a dangerous disease which is one of the main causes of death in the world, which is 8.8 million deaths in 2015. A new method has been developed for the treatment of cancer with small side effects, Boron Neutron Capture Therapy (BNCT). BNCT is based on the ability of non-radioactive isotopes Boron-10 to capture thermal neutrons. Boron is the main key of the BNCT process wherein, radiation of cancer cells can be carried out selectively if the cancer contains high concentrations of boron. Boron doses in cancer cells cannot be measured directly, therefore artificial network methods are used to compute doses computationally, namely the Monte Carlo method with the Particle and Heavy Ion Transport Code System (PHITS) program . Boron dose used was 10, 20 and 30 ?g/g. It was found that the greater the boron dose the greater the number of neutrons absorbed. The results showed that the largest absorption dose occurred in the Gross Tumor Volume (GTV) area of ??7.7076E-10 Gy/cm 2 . Key words: Cancer, BNCT, Dose of Boron, PHITS.